Comparitive Studies on Antimicrobial Activity of Ulva reticulata and Ulva lactuca against Human Pathogens - Kolanjinathan, K. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACTMarine algae are not only the primary and major producers of organic matter in the sea, but they also exert profound effects on the density and distribution of other inhabitants of the marine environment. The present study was conducted to compare the antimicrobial activity of Ulva reticulata and Ulva lactuca solvent extracts against human pathogenic bacteria and fungi. The seaweeds Ulva reticulata and Ulva lactuca were collected and powdered. The powdered material was extracted using the organic solvents viz., methanol, acetone, chloroform, hexane and ethyl acetate. Antimicrobial activity of Ulva reticulata and Ulva lactuca solvent extracts was determined by Disc diffusion method. Among the solvents tested, methanol extract showed maximum inhibitory activity than other solvents. The results also indicated that scientific studies carried out on medicinal plants having traditional claims of effectiveness might warrant fruitful results. These plants could serve as useful source of new antimicrobial agents.